2011
DOI: 10.1029/2011gl047929
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in pan-evaporation dynamics in China

Abstract: [1] Pan-evaporation (E pan ) as the indicator of atmospheric evaporative demand has decreased worldwide with climate change in the last decades, which is called "Pan Evaporation Paradox". This study investigates the recent changes in E pan dynamics in China using the observed E pan records for the period 1960-2007. The records show that E pan decreased in China from 1960 to 1991 by −5.4 mm yr −2 . The attribution results show that the significant decreases (P < 0.001) in wind speed and solar radiation offset t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
135
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 18 publications
22
135
4
1
Order By: Relevance
“…The decreasing ET 0 trend also was found in the Beijing-Tianjin Sand Source Control Project Region in China from 1959 to 2011 (Shan et al 2015). Liu et al (2011) reported that pan evaporation decreased in China from 1960 to 1991 while increased from 1992 to 2007. Much longer series of observation data are required to analyze how the phenomenon of "evaporation paradox" will change in future .…”
Section: Discussionmentioning
confidence: 79%
“…The decreasing ET 0 trend also was found in the Beijing-Tianjin Sand Source Control Project Region in China from 1959 to 2011 (Shan et al 2015). Liu et al (2011) reported that pan evaporation decreased in China from 1960 to 1991 while increased from 1992 to 2007. Much longer series of observation data are required to analyze how the phenomenon of "evaporation paradox" will change in future .…”
Section: Discussionmentioning
confidence: 79%
“…In this study, the relationship between potential evapotranspiration and air temperature, solar radiation, wind speed and vapour pressure are described based on the Penman-Monteith equation. So the change in potential evapotranspiration can be estimated as (Liu et al 2011):…”
Section: Analytical Methods To Separate the Effects Of Climate Change mentioning
confidence: 99%
“…The nonparametric Mann-Kendall test (Kendall 1975;Mann 1945) was conducted to determine whether the trend of the regression line was significant, which was widely used for trend detection due to its robustness for non-normally distributed data (Belle and Hughes 1984;Partal and Kahya 2006;Abarghouei et al 2011;Liu et al 2011). For a given data series composed of X 1 , X 2 …X n , their ranks are R 1 , R 2 … R n , and the Mann--Kendall rank statistic (S) is calculated as:…”
Section: Methodsmentioning
confidence: 99%